THALLIUM ISOTOPE VARIATIONS IN SEAWATER AND HYDROGENETIC, DIAGENETIC, AND HYDROTHERMAL FERROMANGANESE DEPOSITS - Rehkamper M.; Frank M.; Hein J.R.; Porcelli D.; Halliday A.; Ingri J.; Liebetrau V. (My University, 2002)
Results are presented for the first in-depth investigation of Tl isotope variations in marine materials. The Tl isotopic measurements were conducted by multiple collector-inductively coupled plasma mass spectrometry for a comprehensive suite of hydrogenetic ferromanganese crusts, diagenetic Fe-Mn nodules, hydrothermal manganese deposits and seawater samples. The natural variability of Tl isotope compositions in these samples exceeds the analytical reproducibility (+/-0.05%%) by more than a factor of 40. Hydrogenetic Fe-Mn crusts have ε205Tl of +10 to +14, whereas seawater is characterized by values as low as -8 (ε205Tl represents the deviation of the 205Tl/203Tl ratio of a sample from the NIST SRM 997 Tl isotope standard in parts per 104). This ~2%% difference in isotope composition is thought to result from the isotope fractionation that accompanies the adsorption of Tl onto ferromanganese particles. An equilibrium fractionation factor of α~1.0021 is calculated for this process. Ferromanganese nodules and hydrothermal manganese deposits have variable Tl isotope compositions that range between the values obtained for seawater and hydrogenetic Fe-Mn crusts. The variability in ε205Tl in diagenetic nodules appears to be caused by the adsorption of Tl from pore fluids, which act as a closed-system reservoir with a Tl isotope composition that is inferred to be similar to seawater. Nodules with ε205Tl values similar to seawater are found if the scavenging of Tl is nearly quantitative. Hydrothermal manganese deposits display a positive correlation between ε205Tl and Mn/Fe. This trend is thought to be due to the derivation of Tl from distinct hydrothermal sources. Deposits with low Mn/Fe ratios and low ε205Tl are produced by the adsorption of Tl from fluids that are sampled close to hydrothermal sources. Such fluids have low Mn/Fe ratios and relatively high temperatures, such that only minor isotope fractionation occurs during adsorption. Hydrothermal manganese deposits with high Mn/Fe and high ε205Tl are generated by scavenging of Tl from colder, more distal hydrothermal fluids. Under such conditions, adsorption is associated with significant isotope fractionation, and this produces deposits with higher ε205Tl values coupled with high Mn/Fe.
Keywords: STABLE ISOTOPES; ISOTOPE FRACTIONATION; THALLIUM; FERROMANGANESE COMPOSITION; SEA WATER